The Effectiveness of the Role of the National Narcotics Agency (BNN) of South Sulawesi Province in the Recovery and Social Reintegration of Drug Abusers - Jumadil Awal; La Ode Husen; Agussalim A Gadjong (Al-Ishlah: Jurnal Ilmiah Hukum, 2026)
This study analyzes the effectiveness of the role of the National Narcotics Agency (BNN) of South Sulawesi Province in implementing recovery (rehabilitation) and social reintegration programs for drug abusers. It employs an empirical juridical (socio-legal) approach with a descriptive-analytical design and qualitative method, using data from interviews, observation, and documentation involving key stakeholders. The findings show that BNN’s role has been relatively effective, reflected in comprehensive, structured, and sustainable rehabilitation programs that embody a shift from a repressive to a humanistic and restorative approach. Effectiveness is indicated by behavioral changes among clients, reduced relapse rates, and increased social acceptance supported by family, community, and inter-agency collaboration. Nonetheless, effectiveness is influenced by legal frameworks, law enforcement, facilities, societal attitudes, and legal culture, with limitations in human resources, budget, and infrastructure as key challenges. The study concludes that a holistic and integrated approach is essential, with strengthened institutional capacity, improved facilities, increased public awareness, and expanded community-based programs to support sustainable reintegration and reduce drug abuse